Genetics of rotator cuff tears: no association of col5a1 gene in a case-control study - Umile Giuseppe Longo; Katia Margiotti; Stefano Petrillo; Giacomo Rizzello; Caterina Fusilli; Nicola Maffulli; Alessandro De Luca; Vincenzo Denaro (BMC, 2018)
Abstract Background The incidence of RC tears increases with aging, affecting approximately 30 to 50% of individuals older than 50 years, and more than 50% of individuals older than 80 years. Intrinsic factors (age or gender), extrinsic factors (sports activity or occupation), and biological factors were identified in the onset and progression of RC tears. The attention in the study of aetiology of RC tendinopathy has shifted to the identification of gene variants. Genes encoding for proteins regulating the concentration of pyrophosphate in the extracellular matrix and genes encoding for fibroblastic growth factors, defensin beta 1 and estrogen-related receptor-beta were analyzed. However, only in one study the role of variants of collagen type V alpha 1 (col5a1) gene in RC tears was assessed. The objective of this study was to determine whether a col5a1 DNA sequence variant, rs12722 (C/T) was associated with rotator cuff (RC) tears in a case-control study. Methods The study included 93 Caucasian patients undergoing surgery for RC tears and 206 patients with no history and sign of RC disease as evaluated by MRI. Patients were divided into two groups. Group 1 included patients with RC tear diagnosed on clinical and imaging grounds and confirmed at the time of surgery. Group 2 (control group) included patients without history or clinical symptoms of RC disorders and with a MRI negative for RC disease. DNA was obtained from approximately 1.2 ml of venous blood using the MagCore extractor system H16 with a MagCore Genomic DNA Large Volume Whole Blood Kit (RBC Bioscience Corp., Taiwan). All study participants were genotyped for SNPs rs12722. Results We first estimated that our study had 92% power at p < 0.05 to detect a genetic effect size of 2.05 in the RT tears (93 individuals) and healthy population (206 individuals) cohorts, assuming a minor allele frequency for col5a1 variant rs12722 of 0.5707 in the Italian population (gnomAD frequency). No significant difference in allele and genotype frequencies was observed between RT tears patients and healthy controls. Similarly, no significant association was seen between the RT tears and healthy controls participants in the combined genotype distributions. Conclusion In conclusion, no correlations between the SNP rs12722 of col5a1 gene and RC tears susceptibility was found.